Conceptual Approach On Development of Tidal Farming From Water Management Aspect, A Case Study at Kalimantan, Indonesia - Sahid Susanto; Sigit Supadmo Arif (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1987)
A lot of tidal irrigation land development projects were carried out in several locations of Kalimantan for new settlement and food production. A continuous research has been conducted to develop tidal agricultural land since 1971. Based on the research, a new concept for redesigning and reconstructing of tertiary demonstration block (TDB) should be develop. A conceptual approach on development of tidal farming from water management aspect has been proposed. The concept is presented in a model named Micro Water Management Model (MWMM): The basic concept of MWMM is improvement of micro water management and then be followed by improvement of all aspects.